2021
DOI: 10.3390/en14164888
|View full text |Cite
|
Sign up to set email alerts
|

Polish Local Government’s Perspective on Revitalisation: A Framework for Future Socially Sustainable Solutions

Abstract: The principal goal of this paper is to investigate the views of local government officials on revitalisation priorities in Polish municipalities. To accomplish this, the perception of revitalisation objectives by local government representatives (who, according to Polish regulations, are responsible for revitalisation planning and carrying it out) was examined. A catalogue of revitalisation objectives, which were assessed by the respondents, was drawn up on the basis of a review of research on the conceptualis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…We provide other training and consulting services 12 We provide advisory services regarding external financing opportunities for enterprise supporting the preparation of applications for EU funds) 13 Our entrepreneurs benefit from training courses organized by the community 14 We provide information on the community website about initiatives/events/proje development programmes 15 We provide information on the community website about available premises/real est regardless of whether they belong to public or private entities) 16 We provide information about available common (co-working) spaces available to entre of whether they belong to public or private entities) 17 We provide information on the community website about current competitions enablin innovative activities, such as vouchers for innovation Institutional Review Board Statement: Not applicable.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…We provide other training and consulting services 12 We provide advisory services regarding external financing opportunities for enterprise supporting the preparation of applications for EU funds) 13 Our entrepreneurs benefit from training courses organized by the community 14 We provide information on the community website about initiatives/events/proje development programmes 15 We provide information on the community website about available premises/real est regardless of whether they belong to public or private entities) 16 We provide information about available common (co-working) spaces available to entre of whether they belong to public or private entities) 17 We provide information on the community website about current competitions enablin innovative activities, such as vouchers for innovation Institutional Review Board Statement: Not applicable.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Local government (LG) is increasingly involved in supporting entrepreneurship and local development [8]. The role of LG in local development has been widely discussed in research studies [9][10][11][12][13][14][15], which have pointed out that local, regional, and national entrepreneurial development programming is complex, dependent on the type of organization and stakeholders involved, and requires coordination. The research findings published in [16] indicated that policy makers need to understand the role of public sector institutions in the creation of local entrepreneurship, as this role can extend into innovative leadership in governance of enterprises and entrepreneurship at the local and regional tiers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the contemporary global landscape, sustainable development is increasingly central to urban planning and growth management, as highlighted in recent studies on sustainable cities (Przywojska 2021). Revitalization, which focuses on enhancing city identities, conserving resources, fostering economic development, and elevating the quality of life, is considered integral to sustainability (Ragheb & Ragheb 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Engage the community: Engaging the community is critical for the success of revitalisation efforts. Community engagement can involve public meetings, workshops, and surveys to gather input and feedback from residents and to encourage participation in revitalisation initiatives [13,[22][23][24][25].…”
mentioning
confidence: 99%